A Comparison and Prediction of Irrational Beliefs and Cognitive Functioning Among Depressed and Non-Depressed Adults in Gujrat, Pakistan - Naz, Iram; Ahmed, Laiba; Ishaq, Amna; Ayyaz, Maryyam (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare and predict the irrational beliefs and cognitive functioning among depressed and non-depressed adults in Gujrat, Pakistan.Study Design: Comparative cross-sectional study.Place and Duration of Study: Zulfiqar Hospital, Akram Hospital and Aziz Bhatti Hospital, Gujrat and Department of Psychology, the University of Gujrat from Dec 2017 to Mar 2018.Methodology: The data was collected from 200 adults, 100 depressed adults and 100 non-depressed adults using consecutive sampling. The non-depressed adults with no past psychiatric history were recruited from the community. The irrational beliefs were assessed using the Evaluative beliefs scale, and cognitive functioning was measured using the Montreal cognitive assessment scale.Results: The independent sample t-test indicated that there was a statistically significant difference (p